Cycling Fading Mechanism for a Bismuth Fluoride Electrode in a Lithium‐Ion Battery. Issue 12 (27th April 2017) - Konishi, Hiroaki; Minato, Taketoshi; Abe, Takeshi; Ogumi, Zempachi
Abstract: The nanocomposite of BiF3 and carbon (BiF3 /C) is a promising cathode material for lithium‐ion batteries because of its high capacity. When BiF3 /C was charged and discharged within voltage range of 2.0–4.5 V, the BiF3 /C exhibited high capacity; however, as the cycle progressed, the discharge‐charge capacities decreased and the charge voltage shifted towards higher region. When charge cut‐off voltage was changed from 4.5 to 3.5 V, the capacity degradation was suppressed. This indicates that the cause of capacity degradation was attributed to the isolation of active material from conductive network due to the large volume change. In contrast, when discharge cut‐off condition was limited to 150 mAh g –1, the shift of charge voltage was suppressed. The results obtained by atomic force microscopy (AFM) and X‐ray photoelectron spectroscopy (XPS) indicate that the surface product which was formed by the reaction between electrolyte and Bi formed during the discharge process. Abstract : The cycling fading mechanism for BiF3 /C electrode in lithium‐ion battery was investigated. During the discharge process, BiF3 was partly isolated due to large volume change; therefore. the capacity was decreased. Further, the surface product was formed on the Bi metal surface in the discharge state due to high reactivity of metal with electrolyte. This caused the shift of charge voltage.